Ray Tracing Complex Models Containing Surface Tessellations - Snyder, John; , Alan H. Barr (ACM SIGGRAPH, 1987)
An approach to ray tracing complex models containing mathematically defined surfaces is presented. Parametric and implicit surfaces, and boolean combinations of these, are first tessellated into triangles. The resulting triangles from many such surfaces are organized in a hierachy of lists and 3D grids, allowing efficient calcu]atlon of ray/model intersections. The technique has been used to ray trace models containing billions of triangles and surfaces never before ray traced. The organizing scheme developed is also independently useful for efficiently ray tracing any complex model, whether or not it contains surface tessellations.